STUDI PERBANDINGAN ALTERNATIF PENINGGIAN ELEVASI JALAN DENGAN PENGGUNAAN BANGUNAN PROTEKSI PIPA TERHADAP BIAYA, MUTU DAN WAKTU - fauziyah, shifa; Nurjihad C, Fajar; Suwarto, Fardzanela (Civil Infrastructure Engineering and Architectural Design, 2019)
One of the work items in the Soekarno-Hatta Airport Accessibility and Ducting Utility Project is widening the M1-M2 road. Pit test results in that area indicate that there is a 40 cm (16